Influence of the femoral offset on the muscles passive resistance in total hip arthroplasty. - Stanisław Burzyński; Agnieszka Sabik; Wojciech Witkowski; Piotr Łuczkiewicz (PLoS ONE)
Background Soft tissue tension is treated as a crucial factor influencing the post-THA dislocation. The femoral offset is regarded as one of the major parameters responsible for the stabilization of the prosthesis. It is unclear which soft tissue is mostly affected by the offset changes. Methods A finite element model of the hip was created. The model comprised muscles, bones, a stem, the acetabular component and a liner. The muscles were modelled as a Hill-type musculo-tendon nonlinear springs. Nonlinear analyses of the hip flexion and internal rotation were performed for the two values of the femoral stem offset. Results We observed that the quadratus femoris and gluteus medius produce the largest resisting moment opposing the external load excreted by the surgeon during the intraoperative hip dislocation test. Conclusions An increased femoral offset increases the stretching of the quadratus femoris muscle significantly and provides the growth of its initial passive force. This muscle serves as a stiff band, providing stabilisation of the hip prosthesis, measured during the simulated intraoperative test.